Menstrual and reproductive factors, exogenous hormone use, and gastric cancer risk in a cohort of women from the European Prospective Investigation Into Cancer and Nutrition. - Duell, E; Travier, N; Lujan-Barroso, L; Boutron-Ruault, M; Clavel-Chapelon, F; Palli, D; Krogh, V; Mattiello, A; Tumino, R; Sacerdote, C; Rodriguez, L; Sanchez-Cantalejo, E; et al. (2010)
The worldwide incidence of gastric adenocarcinoma (GC) is lower in women than in men. Furthermore, cancer patients treated with estrogens have been reported to have a lower subsequent risk of GC. The authors conducted a prospective analysis of menstrual and reproductive factors, exogenous hormone use, and GC in 335,216 women from the European Prospective Investigation Into Cancer and Nutrition, a cohort study of individuals aged 35-70 years from 10 European countries. After a mean follow-up of 8.7 years (through 2004), 181 women for whom complete exposure data were available developed GC. Adjusted hazard ratios and 95% confidence intervals were estimated using Cox proportional hazards models. All statistical tests were 2-sided. Women who had ovariectomy had a 79% increased risk of GC (based on 25 cases) compared with women who did not (hazard ratio = 1.79, 95% confidence interval: 1.15, 2.78). Total cumulative years of menstrual cycling was inversely associated with GC risk (fifth vs. first quintile: hazard ratio = 0.55, 95% confidence interval: 0.31, 0.98; P(trend) = 0.06). No other reproductive factors analyzed were associated with risk of GC. The results of this analysis provide some support for the hypothesis that endogenous ovarian sex hormones lower GC incidence in women.